Information sourcing by dog owners in the UK: Resource selection and perceptions of knowledge. (6th November 2021) - Kuhl, Christina Ann; Dean, Rachel; Quarmby, Caroline; Lea, Richard Graham
Abstract: Background: Dogs are a popular pet in the UK. Information resources utilised by dog owners can influence welfare at acquisition and throughout a dog's lifetime. This study determined where UK dog owners source information, and how perceptions relating to pedigree dog breeding and health may influence this process. Methods: This cross‐sectional study used online questionnaires to explore the information resources used by dog owners and their perceptions of veterinary surgeons' and dog breeders' knowledge. Results: Overall, 1336 responses were collected (useable responses: 1167). Data indicated most owners conducted research before getting a dog, with the internet, books, breeders and friends or family among the most popular resources used. Preferred sources of information during a dogs' lifetime included the internet, talking to veterinary surgeons and reading books. Veterinary surgeons were the most popular source for health advice. Pedigree dog owners perceived veterinary surgeons and breeders to be equally knowledgeable on canine inherited diseases. However, veterinary surgeons were perceived as being more knowledgeable on inherited disease screening programmes and breeders more knowledgeable on dog breeding. Conclusion: This study highlights the information resources preferred by dog owners, providing an opportunity to maximise access to reliable sources of information to improve dog welfare.